Toward an Agenda for Improving Wastewater Use in Agriculture - Scheierling, Susanne M.; Bartone, Carl R.; Mara, Duncan D.; Drechsel, Pay (Taylor and Francis, 2013)
This paper sets out the trends and challenges of wastewater use in agriculture; identifies the risks and benefits of wastewater irrigation; describes the risk-assessment and management framework adopted by the World Health Organization, the Food and Agriculture Organization of the United Nations and other international and national organizations; and proposes measures for applying the framework to reduce health risks by moving from unplanned to a planned, integrated, approach to wastewater use for irrigation.